Political crises, social conflict and economic development : the political economy of the Andean Region - Solimano, Andres (UK : Edward Elgar, 2005)
The contributors to this authoritative volume analyze the impact of political crises and social conflict on economic performance in the Andean region of Latin America. The blend of theory and case studies is also relevant for understanding other complex societies in the developing world and transition economies
Includes references and index.
Keywords: Andes Region Politics and government; Region Economic conditions